1984
DOI: 10.1161/01.cir.70.5.806
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous oxygen tension and capillary morphologic characteristics and density in patients with chronic venous incompetence.

Abstract: The transparent oxygen electrode, recently developed by Huch and his co-workers, permits monitoring of transcutaneous oxygen tension (tcPo2) at defined sites on the capillaroscopic image obtained by videomicroscopy. This combined system has been applied to study the nutritional skin capillaries of patients with chronic venous incompetence (CVI). 806 simultaneous measurement of the oxygen tension of the skin (tcPo2) and examination of the nutritional skin capillaries at the monitoring site by videomicroscopy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
0
3

Year Published

1987
1987
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(101 citation statements)
references
References 7 publications
1
97
0
3
Order By: Relevance
“…10,33 Sustained hypertension at the capillary level is associated with many morphologic changes including elongation and dilation of the capillary bed, increased surface area of the endothelium, increased type IV collagen in the basement membrane, and the formation of a pericapillary fibrin cuff. 12,[34][35][36][37] These abnormal capillaries are more permeable to large molecules, including fibrinogen, 38 and it has been hypothesized that leaked fibrinogen is converted to fibrin in the pericapillary space. 37,38 Other studies have shown that the fibrinolytic activity of blood and tissues is deficient in patients with lipodermatosclerosis, resulting in a decreased clearance of fibrin.…”
Section: Pathophysiologymentioning
confidence: 99%
“…10,33 Sustained hypertension at the capillary level is associated with many morphologic changes including elongation and dilation of the capillary bed, increased surface area of the endothelium, increased type IV collagen in the basement membrane, and the formation of a pericapillary fibrin cuff. 12,[34][35][36][37] These abnormal capillaries are more permeable to large molecules, including fibrinogen, 38 and it has been hypothesized that leaked fibrinogen is converted to fibrin in the pericapillary space. 37,38 Other studies have shown that the fibrinolytic activity of blood and tissues is deficient in patients with lipodermatosclerosis, resulting in a decreased clearance of fibrin.…”
Section: Pathophysiologymentioning
confidence: 99%
“…11 P tc O 2 values % 40 mm Hg are typically considered indicative of hypoxia capable of inhibiting wound healing. 12,13 The levels near the patient's non-healing ulcers were in this range as documented in Table 1. In addition, these levels improved dramatically while breathing 100% oxygen at 1 ATA.…”
Section: Tcoms In Hbomentioning
confidence: 80%
“…The barrier function of the capillary wall is impaired, leading to the formation of micro-oedema, evidenced by a pericapillary ' halo '-like appearance after intravenous injection of sodium fluorescein [3,[61][62][63]. This halo, which is caused by a unique microoedema in the skin papillae, can be clearly demonstrated by capillaroscopy, especially after intravenous injection of sodium flourescein [63,64]. The oedema, which contains fibrin, proteins, and neutral polysaccharides [65], blocks the flow of nutrients between the capillaries and the skin cells and is probably the main reason for the abolished nutrition of the affected skin [63,66].…”
Section: Chronic Venous Insufficiencymentioning
confidence: 99%